2021
DOI: 10.1021/acsami.1c03622
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Hybrid Photo-Thermoelectric Generator Based on Single Thermoelectric Effect for Simultaneously Harvesting Thermal and Radiation Energies

Abstract: Wearable electronic devices have great potential in the fields of the Internet of Things (IoT), sports and entertainment, and healthcare, and they are essential in advancing the development of next-generation electronic information technology. However, conventional lithium batteries, which are currently the main power supply of wearable electronic devices, have some critical issues, such as frequent charging, environmental pollution, and no surface adaptability, which limit the further development of wearable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 48 publications
1
22
0
Order By: Relevance
“…43 A very high output power of 8.3 and 15.8 mW can be reached when this PTEG is irradiated with light intensities of 100 and 150 mW cm À2 , respectively. The power enhancement of the PTEG can be easily obtained by increasing the number of legs, so the singleleg output power of 2.1 and 4.0 mW with light intensities of 100 and 150 mW cm À2 of this device is used to compare it with the vast majority of the currently reported PTEGs, 13,40,42,43,[56][57][58] as shown in Fig. 5g.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…43 A very high output power of 8.3 and 15.8 mW can be reached when this PTEG is irradiated with light intensities of 100 and 150 mW cm À2 , respectively. The power enhancement of the PTEG can be easily obtained by increasing the number of legs, so the singleleg output power of 2.1 and 4.0 mW with light intensities of 100 and 150 mW cm À2 of this device is used to compare it with the vast majority of the currently reported PTEGs, 13,40,42,43,[56][57][58] as shown in Fig. 5g.…”
Section: Resultsmentioning
confidence: 99%
“…(e) Output voltage and (f) power versus current at different NIR light radiation powers. (g) Comparison ofthe single-leg output power of the PTEG in our work with that in reported studies 13,40,42,43,[56][57][58]. (h) Open-circuit output voltages of the device at different intensities of visible light irradiation.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…However, silk I converts to a β-sheet-rich silk II conformation due to the effect of organic solvents, temperature, shear stress, pH, and concentration, which causes the final material to be stiff with high tensile strength and slow degrading nature. Yu et al showed that RSF undergoes conformational alteration at a shallow concentration (0.1 mg mL –1 ) and suggested a nucleation-dependent aggregation process that involved the shear-induced transition of the random coil to the β-strand, which further converts into β-sheets . RSF has been processed in different forms of materials, e.g., hydrogels, sponges, films, fibril-based mats, nanoparticles, and especially silk fibroin films have been extensively used in electronics. RSF-based films have been made using spin coating and dry casting techniques, where the dry-cast films are mechanically less robust and brittle and the spin-coated films provide better mechanical toughness (∼32 kJ m –3 ) with an ultimate tensile strength of 100 MPa but still with a high degree of brittleness (breaking strain was found in between 0.5 and 3%). This limits their applicability in (human bone marrow stromal cells) growth and attachment. ,, Furthermore, RSF-based hydrogels have been fabricated via sol–gel transformation induced via various methods including sonication, heat/cold treatment, osmotic stress, and pH.…”
Section: Introductionmentioning
confidence: 99%
“…The electrical energy can be from as low as nanowatts to a few watts, making it suitable for a wide range of applications. Some of the applications include the following: in space, integration with gas turbine, standalone solar TEG, combined with photovoltaic to generate additional electrical energy, , and powering of portable electronic devices and wearable sensors. Thermoelectric generators are lightweight, can be rigid or flexible, and operate quietly day and night since they do not have moving parts. Additionally, they have no gas emission, no vibration, and a long lifespan .…”
Section: Introductionmentioning
confidence: 99%